2019
DOI: 10.1097/md.0000000000015665
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic treatment for cervical ligamentum flavum gouty tophus

Abstract: Rationale: Cervical ligamentum flavum gout (CLFG) is relatively rare, and its clinical manifestations are complicated; hence, it is often confused with ligamentum flavum ossification. Gout tophi may relate to certain risk factors, such as renal insufficiency and lack of long-term effective uric acid treatment. Patient concerns: A 73-year-old man had a half-year history of left upper extremity pain and numbness, which was aggravated 6 months ago. Diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Once the intraspinal tophi picture is established, it is essential to assess the patient comprehensively and provide adequate treatment. If the patient has a spinal cord or root compression that produces progressive neurological deterioration, surgical decompression of the spinal canal could be necessary [ 3 , 16 , 20 ]. The surgical removal of gout tophi usually yields good results.…”
Section: Discussionmentioning
confidence: 99%
“…Once the intraspinal tophi picture is established, it is essential to assess the patient comprehensively and provide adequate treatment. If the patient has a spinal cord or root compression that produces progressive neurological deterioration, surgical decompression of the spinal canal could be necessary [ 3 , 16 , 20 ]. The surgical removal of gout tophi usually yields good results.…”
Section: Discussionmentioning
confidence: 99%
“…DECT has an advantage in the qualitative detection and overall evaluation of the gout source, and can detect gout deposited in atypical sites such as the spine [ 13 , 14 ]. A meta-analysis [ 15 ] showed that the sensitivity and specificity of DECT were 87% and 84%, respectively, compared with the pathological diagnosis of sodium urate crystal deposition as gold standard. The DECT of our case also supports the diagnosis of spinal gout tophi preoperatively.…”
Section: Discussionmentioning
confidence: 99%